Respostas neuromusculares e bioquímicas entre indivíduos com doença pulmonar obstrutiva crônica (DPOC) e saudáveis - Queiroz, Natércia Ferreira de (2017)
Objective: To compare neuromuscular and biochemical responses of femoral quadriceps muscle damage and fatigue among COPD and healthy individuals. Methods: This was an observational, cross-sectional and comparative study. The sample consisted of 18 individuals allocated to two distinct groups: COPD Group (GD) and Healthy Group (GS) who were evaluated through lung function; of the neuromuscular performance of the quadriceps; The biochemical markers of muscle damage and fatigue; fatigue and muscle pain. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 20.0 with a significance level of 5%. Results: There was a statistically significant difference in the power between GD and GS (99.0 vs 145.1; p = 0.02) and a tendency to the difference in total work, respectively (1,035.5 vs 1,671.5; p = 0.06) between groups. In the analysis of the biochemical marker, LDH, for muscle fatigue was observed a significant difference between the groups immediately after the isokinetic test in the quadriceps (402.3 vs 289.4; p = 0.03). Conclusions: The neuromuscular and biochemical responses of femoral quadriceps muscle damage and fatigue in COPD are diminished in the study population.